Evaluación de la remoción de contaminantes del sistema de islas flotantes artificiales (Ifa) con pasto guinea (Panicum maximum) a través de un modelo matemático, periodo 2019 – 2020. - Aragón López, Erick Gabriel (2020)
Artificial floating islands (AFI) are an ecotechnological and innovative alternative designed to capture pollutants present in water bodies. The objective of the current research work was to evaluate the Guinea grass (Panicum maximum) as possible specie for phytoremediation of contaminated water with excess nutrients. The removal evaluation was analyzed every 21 days for a period of 3 months, based on four parameters: nitrates (NO3), phosphates (PO4), biochemical oxygen demand (BOD5) and hydrogen potential (pH). Applying pollutant charge removal equation, 91% of NO3 and 0% of PO4 were obtained as result. In addition, the simple linear regression mathematical model determined that, after 16 days, the grass began with the 4.28% removal of NO3, through the RStudio computer program, which relates time to removal.